Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan Kereta Commuter Line Jabodetabek: The Influence of Service Quality and Customer Satisfaction on Customer Loyalty of Jabodetabek Commuter Line Trains - Agnes Darmayanti; Susanti (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Customer loyalty is a customer's commitment to continue using a service based on the experience gained from service quality and the level of satisfaction perceived. This study aims to determine the effect of service quality and customer satisfaction on customer loyalty of the Jabodetabek Commuter Line train. A quantitative method was employed by distributing questionnaires to 100 respondents who use the Jabodetabek Commuter Line, with data analyzed using validity, reliability, and classical assumption tests (normality, multicollinearity, heteroscedasticity), multiple linear regression analysis, and hypothesis testing (t-test, F-test, and coefficient of determination). The t-test results show that the Service Quality variable obtained a t-value of 6.848 > 1.984 with a significance of 0.000 < 0.05, while the Customer Satisfaction variable obtained a t-value of 8.604 > 1.984 with a significance of 0.000 < 0.05, indicating both have a positive and significant effect on Customer Loyalty. The F-test shows an F-value of 54.262 > 3.09 with a significance of 0.000 < 0.05, indicating a simultaneous significant effect. The coefficient of determination (R²) is 0.528 (52.8%), meaning both variables explain 52.8% of Customer Loyalty, while the remaining 47.2% is influenced by other variables not examined in this study.